Consuming hunger [videorecording] part 2 - shaping the image.
Second part of two documentaries which looks at the way in which the "story" of the famine in Ethiopia became national news in Britain and everyone's imagination. This episode focuses on the world wide media spectaculars inspired by Bob Geldof and asks to what extent these events were a celebration of rock "n" roll and the power of music stars and TV authorities, rather than why hunger exists in a world of plenty.